THE USING OF YOUTUBE MEDIA IN IMPROVING THE ENGLISH ABILITY OF STUDENTS IN CLASS XI IPA SMA NEGERI 9 REJANG LEBONG - Zulhijah - (Universitas Samudra, 2020)
This study aims to improve English language skills by using Youtube. The research sample is students of class XI Science 1 consisting of 27 students. The stages of the research consisted of Planning, Implementation, Observation and Reflection. The results showed an increase in English proficiency, this was seen in the first cycle only 20 students who had grades above the KKM with an average grade of 82.7 and classical completeness of 74.07%. In cycle II there were 24 students who had grades above the KKM with the average value of students increasing to 86.33 with a classical completeness of 88.88%.